Service companies in Latin America: an exploratory study about determinants of international competitiveness, obstacles and public policies - López, Andrés (2017)
Services have long been a dominant sector in the global economy, since they account for the bulk of gross domestic product and employment, both in developed economies and in much of the developing world. In recent years, in turn, services have increased their weight in both international trade and external investment flows. Although Latin American companies have begun to actively participate in this new global dynamic and several countries of the region show a significant dynamism in their services exports, there are still important spaces to deepen these trends and scale positions. The present work is based on a survey of service companies in Latin America in which they were inquired about their own views about obstacles to trade in services, as well as on the coverage and impact of public policies in force that influence this trade. From this, some useful policy guidelines can be derived to promote the development of services exports in Latin America.